Social Innovation in Poverty Reduction Through the Program for Construction of Unliable Housing in Central Java Province - Pratisto Nugroho; Hardi Warsono; Sri Puryono; Kismartini Kismartini (Budapest International Research and Critics University, 2022)
Paunescu (2014:106) states that social innovation can be used to approach social problems to bring about gradual change by a particular group of people or to overcome deep structural problems, which require change quickly and affect many people which have a scale of impact on, for example, unemployment or unemployment. poverty. This study aims to analyze and describe the implementation of social innovation in poverty alleviation through the Social Rehabilitation Program for Uninhabitable Houses in Central Java. By using qualitative research methods, and purposive techniques in determining informants. The results of the study indicate that social innovation through the improvement of uninhabitable houses for the poor carried out by the Central Java Provincial Government has not been optimal. Where the number of poor people in Central Java is still high (3,867.42 thousand people) with a percentage of 11.9% still above the national average, and uninhabitable houses that have not been handled are still 1,584,252 buildings. This is because there are still many internal and external parties who intervene on the authority of the leadership and data verifier officers in determining the community as recipients of the Social Rehabilitation program for Uninhabitable Houses in Central Java Province. And do not make the value of togetherness in building or repairing uninhabitable houses in the community, even though regulations, budgets, and other supporting infrastructure have been prepared by the Central Java Provincial Government to reduce poverty through the current housing improvement program.